A Robust PID Autotuning Method Applied to the Benchmark PID18. Issue 4 (2018) - Zhao, Shiquan; Cajo, Ricardo; Ionescu, Clara M.; De Keyser, Robin; Liu, Sheng; Plaza, Douglas
Abstract: In this paper a proportional-integral-derivative (PID) autotuning control strategy is presented and applied to the benchmark system presented at the 3 rd IFAC Conference on Advances in Proportional-Integral-Derivative Control (PID18). The automatic tuning of controller gains is based on a single sine test, with user-defined robustness margins guaranteed. Its performance is compared against a model based designed controller with computer-aided design tool based on frequency response (FRtool) and against the benchmark reference controller. The closed loop control simulations, applied on the benchmark, indicate that the method properly performed.